THE COMPARISON OF PERFORMANCE AMONG NINE BIGGEST BANKS IN INDONESIA BEFORE AND AFTER THE IMPLEMENTATION OF INDONESIA BANKING ARCHITECTURE - Wijaya, Krisna; Akyuwen, Roberto (KINERJA, 2013)
Like in many countries, banking industry in Indonesia is more dynamic in the last decade. Level of marketcompetition among banks tends to increase continuously. This phenomenon has encouraged banks to createthe more advanced products and services to fulfi ll the growing needs of modern banking customers. Asthe monetary authority, Bank Indonesia has launched the Indonesia Banking Architecture to manage thesedynamics. IBA is a fundamental framework of banking system and provides a direction for banking operationalin Indonesia within 5 to 10 years. It is expected that IBA will create conducive environment which will enablebanks to improve their performance. This research is aimed to compare and analyze the performance of ninebiggest banks in Indonesia before and after the implementation of IBA in 2004. The performance indicatorsused are including ROA, ROE, NIM, CAR, LDR, and NPL. The data on these indicators are collected in theperiod of 2000-2009. The period of 2000-2004 is considered as before the implementation of IBA, while 2005-2009 is defi ned as after the implementation of IBA. The main tool of analysis used in this research is the meanequality test.Keywords: bank, Indonesia Banking Architecture, performance.